Control of Diabetes mellitus and hypertension in people affiliated to the Seguro Popular. The case of residents of rural towns in Tabasco, Mexico - Montero Mendoza, Elda (2014)
This article discusses the results of a study designed with the objective to know about the attention that receive at a first level clinics the persons with a diagnosis of diabetes mellitus or hypertension and SeguroPopular insurance. Methodology: The study was in three towns of Nacajuca, Tabasco, México with less than 1,200 inhabitants and 98.4 per cent in indigenous households. The information was gathered from a survey of households; open interviews and informal talks with municipal authorities and allopathic physicians. Through the survey was obtained complete information of 328 households; 107 personas with a chronic disease, 79.4% of them affiliated to the Seguro Popular. The main reported diseases are diabetes mellitus disorders of vision and hypertension. The majority of those interviewed (73.2%) goes to the control of these diseases to the institutional clinic located in or near their town of residence.However, they mention the control as a requirement to meet. Regulated procedures are not followed in health clinics and there is shortage of specific medications so the persons  follow various strategies to acquire the drugs. Conclusions: the treatment and control of hypertension and diabetes mellitus is covered by the catalogue of services that gives the Seguro Popular. Notwithstanding there are deficiencies in compliance with the regulated officially. It is suggested that the public decision-makers in health grant the importance that deserves the first level of health care in the care of chronic diseases.